Sc(OTf)3-Catalyzed Tandem [3+2] Cycloaddition/Nucleophilic Ring-Opening Reaction of Cyclopropane 1,1-Diesters with Azomethine Ylides - Fang, J.; Hu, B.; Ren, J.; Wang, Z.-W. (Asian Journal of Chemistry, 2010)
A new Sc(OTf)3-catalyzed tandem reaction combined with a dimerized self-[3+2] cycloaddition of azomethine ylide and a nucleophilic ring-opening of cyclopropane 1,1-diester has been developed. A series of polyfunctionalized imidazolidine derivatives were synthesized by this reaction (Yield 44-77 %). In some cases, this tandem reaction was also accompanied by a cross- [3+2] cycloaddition of cyclopropane 1,1-diester with imine.